1986
DOI: 10.1002/1097-0142(19860701)58:1<111::aid-cncr2820580120>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Serum deoxythymidine kinase in small cell carcinoma of the lung: Relation to clinical features, prognosis, and other biochemical markers

Abstract: Thymidine kinase (s-TK), lactate dehydrogenase (LDH), and carcinoembryonic antigen (CEA) were determined in pretreatment serum from 125 patients with small cell carcinoma of the lung. The distribution of marker levels into three ranges, when including all patients were as follows: s-TK less than 5 units 49%, 5-less than 10 units 25%, greater than or equal to 10 units 26%; LDH less than 6.7 mukat 31%, 6.7-less than 13.4 mukat 48%, greater than or equal to 13.4 mukat 21%; CEA less than 7.5 micrograms/l 51%, 7.5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

1988
1988
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 20 publications
(2 reference statements)
0
7
0
1
Order By: Relevance
“…Clinical application of the Prolifigen TK-REA technique was previously reported by several authors in patients with malignant disorders and those with non-malignant disorders. [3][4][5][6][7][8][9][10][11][12][13][14][15] Hogberg et al 12 suggested that the bone marrow cells in patients with B 12 deficiency have a defect in DNA synthesis, resulting in the accumulation of immature proliferating bone marrow cells locked at the stage of TK production and release. In a study of patients with untreated B,2 deficiency, serum TK activity was found to be closely correlated with the extent of bone marrow insufficiency, with very high levels being observed in those with the most severe haematological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical application of the Prolifigen TK-REA technique was previously reported by several authors in patients with malignant disorders and those with non-malignant disorders. [3][4][5][6][7][8][9][10][11][12][13][14][15] Hogberg et al 12 suggested that the bone marrow cells in patients with B 12 deficiency have a defect in DNA synthesis, resulting in the accumulation of immature proliferating bone marrow cells locked at the stage of TK production and release. In a study of patients with untreated B,2 deficiency, serum TK activity was found to be closely correlated with the extent of bone marrow insufficiency, with very high levels being observed in those with the most severe haematological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…An improved method for direct quantification of S-TK, based on the use of '25I-lUdR as a substrate, was recently developed by Gronowitz et al 15 Using the improved method, clinical studies have reported elevated S-TK levels in a variety of neoplasias such as breast,16J lung15JS and prostate cancers. 19 s-TK has been found to provide useful therapeutic and prognostic information in a variety hematological disorders such as acute lymphoblastic leukemia,2&22 acute myeloid leukemia,20.2>25 chronic lymphmytic leukemia,2627 non-Hodgkm's lymphorna,2%33 Hodgkm's disease3 and multiple rnyeloma,3538 as reviewed by Hallek et aZ.…”
Section: Serum Thymidine Kinasementioning
confidence: 99%
“…Many enzymes involved in DNA replication increase when the malignant cells enter the S-phase and one of these is deoxythymidine kinase (dTK), which catalyses the phosphorylation of deoxythymidine to deoxythymidine monophosphate. Serum dTK levels are elevated during tissue regeneration, embryonal development, and tumor growth [15-171 and have been demonstrated to have prognostic sigruficance in patients with different types of lymphoma and small-cell lung cancer [18,19]. dTK is widely accepted as a proliferation marker and is thought to reflect the aggressivity and growth dynamics of a malignant lesion.…”
Section: Introductionmentioning
confidence: 99%